(untitled) (International conference on multidisciplinary science, 2023)
this article analyzes socio-economic relations in the provision of public safety. In addition, the meaning of the concept of public safety and its role in the socio-economic development of the society were analyzed. In addition, legal documents in the field of public safety were analyzed.